(untitled) (World Bulletin of Public Health, 2023)
In the Russian Federation, the incidence of NEC is 2-10 children per 1000 premature newborns. At the same time, there is an increase in the incidence in children with low and extremely low body weight. Despite some progress in the diagnosis and treatment of NEC, there are no single specific and sensitive methods that allow early diagnosis and prediction of the development of complications in newborns with NEC. In this study, neonatal necrotizing enterocolitis (NEC) is considered, which is one of the most disabling diseases in preterm and low birth weight infants at gestational age.